Efektivitas metode the power of two Terhadap Prestasi Belajar Pendidikan Agama Islam di SDN lemahbang II sukorejo. - Muhammad Nur Hadi; Siti Inganah; Syaifullah; Elok Lutifati (Mu'allim, 2022)
study aims to analyze how the effectiveness of The Power of Two on learning achievement of Islamic Religious Education subjects in class V SDN Lemahbang Sukorejo. This study uses a quantitative approach. The pre-experimental, namely by using the one group pretest-posttest design. The independent variable in this study is the learning method and the dependent variable is the learning outcomes of the fifth grade students of SDN Lemahbang II Sukorejo. The primary data of this study were obtained from the results of the pre-test and post-test using The Power of Two Method, and the secondary data of this study were sourced from books, journals, previous research and other related sources. The population in this study were all students of class V SDN Lemahbang II Sukorejo, totaling 25 students. The sample used is class V SDN Lemahbang II Sukorejo. In this study, the data collection techniques used were Test and Documentation. The results showed that The Power of Two able to improve student achievement in Islamic Religious Education subjects in class V SDN Lemahbang Sukorejo this was evidenced by the results of the paired sample test , the results of the sig (2-tailed) were 0.000 and it was known that the significance value (2-tailed) of 0.000 < 0.05. The results of this study are expected to be the contribution of education providers to utilize the power of two method in the teaching and learning process in order to be a solution to the problem of student achievement under the KKM.